2006
DOI: 10.1021/ac051624w
|View full text |Cite
|
Sign up to set email alerts
|

TOF-SIMS Analysis Using C60. Effect of Impact Energy on Yield and Damage

Abstract: C60 has been shown to give increased sputter yields and, hence, secondary ions when used as a primary particle in SIMS analysis. In addition, for many samples, there is also a reduction in damage accumulation following continued bombardment with the ion beam. In this paper, we report a study of the impact energy (up to 120 keV) of C60 on the secondary ion yield from a number of samples with consideration of any variation in yield response over mass ranges up to m/z 2000. Although increased impact energy is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
89
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 16 publications
3
89
0
Order By: Relevance
“…Earlier experiments have suggested that multilayer films prepared by Langmuir-Blodgett (LB) techniques might make a good model for more complicated systems [11,12]. Here we show how this technology can be employed to construct samples consisting of multilayers of organic thin films with varying chemical composition.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Earlier experiments have suggested that multilayer films prepared by Langmuir-Blodgett (LB) techniques might make a good model for more complicated systems [11,12]. Here we show how this technology can be employed to construct samples consisting of multilayers of organic thin films with varying chemical composition.…”
mentioning
confidence: 84%
“…Molecular depth profiling of this type has generally not been possible with traditional atomic projectiles due to accumulation of ion-induced damage [9,10]. For bombardment with molecular clusters, however, the chemical damage is often removed as fast as it accumulates, leaving the sample underneath relatively intact [11,12]. Ultimately, three-dimensional mass spectral analysis of complex molecular systems can be achieved with the combination of molecular depth profiling and SIMS imaging [13,14].…”
mentioning
confidence: 99%
“…In a second instance, a thin film of neat dipalmitoyl-phosphatidylcholine (DPPC) has been examined in a similar fashion. This system is of interest since the film is less-well characterized but represents an important class of biomolecules of interest in 3D imaging experiments [20,23]. The results show that in all cases the C 60 ϩ projectile yields larger molecular ion signals than Au 3 ϩ during depth profiling.…”
mentioning
confidence: 99%
“…The gas ion source requires apertures to define the beam size, sacrificing beam current. Recently, a C 60 source has been introduced [20] that achieves a submicron probe size with enough current to acquire images in a reasonable amount of time. In general, however, higher lateral resolution is achieved with the LMIG design if there is enough sensitivity in the mass spectrum associated with the smallest resolvable pixel.…”
mentioning
confidence: 99%
“…One projectile impact at a velocity of a few tens of km/s, or energies≥keV per projectile atom, can generate notable SI emission [18,19]. The critical criterion for projectile selection is the probability of emitting analyte-specific ions.…”
Section: One-on-one Bombardmentmentioning
confidence: 99%